LEGAL PROTECTION AGAINST POST-DIVORCE CHILD SUPPORT OBLIGATIONS IN TERNATE CITY - Gamar Muhdar; Iyam Irahatmi Kaharu; Muhammad Amin Hanafi (RADJA PUBLIKA, 2026)
Article 38 of Law Number 1 of 1974 concerning Marriage and Article 113 of the Compilation of Islamic Law states that divorce is one form of dissolution of marriage other than death and court decisions. Divorce is the severance of the marital bond between a man and a woman as husband and wife, which is carried out before a court hearing, namely the District Court for non-Muslims and the Religious Court for Muslims. This paper aims to analyze: (1) The legal protection for child support obligations after divorce in Ternate City and (2) The efforts that the government can make to reduce the obligation of unpaid alimony after divorce in Ternate City. This research is normative legal research, where the concept of normative legal research. The approaches used in this research are the statute approach and the conceptual approach. The statute approach examines laws and regulations related to the legal issue at hand. This conceptual approach is also used when relevant laws and regulations do not yet or do not address the issue at hand. Children's rights after divorce, both under the Marriage Law and the Compilation of Islamic Law (KHI), include the right to continue receiving care, education, and support from both parents. The father is responsible for the cost of childcare and education after divorce, a term known as